Sheets of branched poly(lactic acid) obtained by one step reactive extrusion calendering process: Melt rheology analysis - J. Cailloux; O. O. Santana; E. Franco-Urquiza; J. J. Bou; F. Carrasco; J. Gamez-Perez; M. L. Maspoch (eXPRESS Polymer Letters, 2013)
One-step reactive extrusion-calendering process (REX-Calendering) was used in order to obtain sheets of 1mm from two PD,L-LA extrusion grades modified with a styrene-acrylic multifunctional oligomeric agent. In a preliminary internal mixer study, torque versus time was monitored in order to determine chain extender ratios and reaction time. Once all parameters were optimized, reactive extrusion experiments were performed. Independently of the processing method employed, under the same processing conditions, PD,L-LA with the lower D enantiomer molar content revealed a higher reactivity towards the reactive agent, induced by its higher thermal sensitivity. REXCalendering process seemed to minimize the degradations reactions during processing, although a competition between degradation and chain extension/branching reactions took place in both processes. Finally, the rheological characterization revealed a higher degree of modification in the melt rheological behaviour for REX-Calendered samples.